Antecedents of Resistance: Populism and the Possibilities for Democratic Globalization - Plante, David J.; Niemi, William L. (2004)
Globalization is often portrayed as a new and unique phenomenon to our times. However, the dependence of American society upon global markets is not new. American Populists of the 19th century faced a similar matrix of political economic constraints. The Populists faced such challenges as the expansion of international trade, a deflationary international monetary order, integrating global capital markets, dependence on credit, and a political system unable to effectively regulate economic activity to public ends. In short, they responded to a system that from their perspective emphasized corporate profits at the expense of democracy. The Populists goal was to create a more democratic political economy in the face of these constraints. Today globalism has been countered by a diverse series of previously unconnected social movements. This paper argues that these movements are part of a rich tradition of democratic responses to the dislocations resulting from attempts to internationalize and commodify all social relations. As such, these 19th century movements offer instruction in the confrontation between democracy and capitalism in its latest iteration. For example, one important continuity between resistance to globalism today, is the use of democratized traditions of moral economy arguments to confront developing inequalities. Successful fair trade alternatives to free trade similarly depend upon moral economy arguments. Despite the inequalities resulting from globalization, challenges from the democratic promise have endured.
Political Science
Keywords: capital market; capitalism; corporate profits; democracy; fair; globalism; globalization; international trade; monetary policy; populism; trade

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Law; Sociology
Keywords: DURKHEIM; Emile; WEBER; Max; 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

Disembedded Liberalism: Why global - Borowiak, Craig (2004)
Bringing together democratic theory and international political economy literatures, I begin with the thesis that economic globalization is undermining the embedded liberalism of the post WWII era. Embodied in the Keynsian welfare state, embedded liberalism held out democratic avenues for disaffected groups to hold political actors responsible for suffering induced by market forces. Transformations in the global economy, however, constrain the options available to governments and curtail avenues of democratic accountability. Some have argued that the market itself can provide an adequate alternative. This view is deeply flawed. Drawing from the economic theory of Hayek and Friedman, I discuss how markets can operate as accountability mechanisms. I then turn to Karl Polanyi to discuss how markets that become disembedded from social contexts induce severe consequences for society and the environment. These consequences exceed what markets alone can account for. What’s more, as Habermas has observed, the system logic of markets is incompatible with the deliberative contexts in which democratic decision-making takes place. To propose markets as the solution to democratic deficits is to miss the point that it is the substitution of markets for social regulation that generates many of the problems in the first place. It is also to ignore the ways markets undermine the very spaces in which legitimate solutions can be determined. Somehow the effects of market accountability need to be accounted for. For this, there can be no substitute for forms of democratic deliberation that are themselves not reducible to market pressures.
Political Science
Keywords: economics; globalization; international relations; liberalism; markets

How likely is a Post-Smithist 21st Century? - Cole, Constance H. (2004)
The current understanding of U.S. hegemony rests on the assumptions of neoclassical theories of both the state and the market. While the service-dominated economy is considered post- Fordist, the rhetoric of the state focuses on institutions of democracy. To what extent is our understanding of democracy dependent on the prior assumptions that the economy is ‘free’? If we reexamine the assumptions about the links between state and economy, drawing on the work of Gramsci, and Polanyi the necessary link between state and economy assumed in our current neoclassical theory looks quite different. The thesis of this research is that hegemonic ideologies of the relationship of state and market reinforce the interests of the commercial class at the expense of any meaningful representation of the working classes. Reconceptualizing the links between state and market in terms of an economics subordinate to social relations beyond those of commercial interests indicates the possibilities of a ‘post- Smithist’ understanding of both the imperfections of neoclassical market theories, and of the narrowness of institutional analyses.
Political Science; International Studies
Keywords: Fordism; Smithism; United States; democracy; economics; economy; hegemony; international; political; post; theory

The Culture War Goes Global: 'Family Values' and the Shape of U.S. Foreign Policy - Kline, Scott (2004)
Examines a neoconservative-religious right nexus that has emerged in and around the Bush White House. Discussion on the work of Karl Polanyi to examine a paradoxical tension that exists between U.S. nationalism and the promotion of a free-market economy; Family values nationalism and free market capitalism; Proposed two areas of critique that have been influenced by the work of Christian realists.
Politcal Science
Keywords: United States; capitalism; economic policy; free enterprise; international studies; nationalism; neo-conservatism; political doctrines

The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Political Science
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science